Palisaded neutrophilic and granulomatous dermatitis associated with the initiation of etanercept in rheumatoid arthritis: a case report - Chia-Lun Chou; Kuo-Hsien Wang; Ying-Yi Chiang (Wolters Kluwer Medknow Publications, 2011)
Palisaded neutrophilic and granulomatous dermatitis (PNGD) is an unusual entity with variable clinical manifestations and histopathological features. It is associated with a variety of immune-mediated systemic diseases, most commonly in rheumatoid arthritis. We report a 42-year-old female with a long-standing history of rheumatoid arthritis, presenting with multiple pruritic erythematous papules and nodules on the lower legs 1 month after beginning treatment with etanercept. Microscopic examination of a fully developed lesion showed a diffuse dense interstitial lymphohistiocytic infiltrate interspersed with palisaded granulomas consisting of epithelioid histiocytes and multinucleated giant cells surrounding central zones of degenerated collagen, neutrophils and leukocytoclastic debris. A diagnosis of PNGD was made on the basis of typical histopathologic features. Withdrawal of etanercept led to gradual resolution of the skin lesions, with no new skin lesions appearing afterwards. Although the correlation between the use of tumor necrosis factor-α (TNF-α) antagonists and the development of PNGD remains controversial and warrants further investigation, PNGD should be considered in the differential diagnosis of skin eruptions within a setting of anti-TNF-α therapy.